Complete genome sequence of Halopiger xanaduensis type strain (SH-6T). Issue 1 (January 2012) - Anderson, Iain; Tindall, Brian; Rohde, Manfred; Lucas, Susan; Han, James; Lapidus, Alla; Cheng, Jan-Fang; Goodwin, Lynne; Pitluck, Sam; Peters, Lin; Pati, Amrita; Mikhailova, Natalia; et al.
Abstract Halopiger xanaduensis is the type species of the genusHalopiger and belongs to the euryarchaeal familyHalobacteriaceae .H. xanaduensis strain SH-6, which is designated as the type strain, was isolated from the sediment of a salt lake in Inner Mongolia, Lake Shangmatala. Like other members of the familyHalobacteriaceae, it is an extreme halophile requiring at least 2.5 M salt for growth. We report here the sequencing and annotation of the 4, 355, 268 bp genome, which includes one chromosome and three plasmids. This genome is part of a Joint Genome Institute (JGI) Community Sequencing Program (CSP) project to sequence diverse haloarchaeal genomes.